Snake phobia among the general population of Tamil Nadu, India. - Anika Salim; Gnaneswar Chandrasekharuni; José R Almeida; Rajendran Vaiyapuri; Harry F Williams; Sundhararajan Arumugam; Subramanian Senthilkumaran; Ketan Patel; Timothy Williams; András Norbert Zsidó; Sakthivel Vaiyapuri (Public Library of Science (PLoS), 2024)
Background A specific phobia is an anxiety disorder that is characterised by persistent and excessive fear in the presence of the object of the phobia. Animal phobias are the most prevalent forms of specific phobia among humans. Fear of snakes (snake phobia) is present in non-human primates which suggests its evolutionary origins as the ability to detect the threat of snakes was critical for survival. Snake phobia is a critical factor in protecting snakes and mitigating snakebite burden. To date, only one standardised psychometric test [the Snake Questionnaire (SNAQ) developed in 1974] has been used to quantify snake phobia although this was not performed in snakebite-endemic countries. In this study, we aimed to determine snake phobia in India, where snakebites and resulting deaths, disabilities and socioeconomic impacts are high. Methodology/principal findings A modified version of the SNAQ (i.e. SNAQ12), which has previously demonstrated internal consistency, excellent reliability, and good discrimination between phobics and non-phobics in Europe was used in this study. SNAQ12 was developed both in English and Tamil and validated by testing on several individuals. Then, the final questionnaire was disseminated to members of the public through various methods including social media and in person through academic and clinical organisations. We received a total of 2032 responses, comprising 1086 [53.4%] males and 946 [46.6%] females, and these data were analysed to determine various aspects of snake phobia in the study population. Conclusions/significance The results demonstrated good internal consistency in using SNAQ12 to determine the phobia amongst the tested population. The data suggests that males are more snake-phobic in all age groups than females in India, in contrast to previous research that suggested that females are usually more snake-phobic. No other critical factors contribute to snake phobia in this study population. The use of the SNAQ12 allowed us to easily discriminate between individuals with phobia and non-clinical controls. This tool can be used as part of the One Health approach to better understand the relationships between snake phobia and snakebites and their impact on the mental health and well-being of vulnerable populations.